Investigation the magnetic properties of CsyCo1-0.5yFe2O4 nanoparticles at low molar ratio variation - Tareq, M.H.; Lafta Sadeq, H.; Hussain Wafaa, A. (Karaganda University named after academician E.A.Buketov, 2023)
The effect of substitution ferrite by previously not used elements to control magnetic properties is of great interest to researchers. This study illustrates the effect of low substitution of Cs, with molar ratios of y of 0.0, 0.05, 0.15, and 0.25 on the structural and magnetic properties of CsyCo1-0.5yFe2O4 nanoparticles. The synthesizing method was the co-precipitation method. The metal chlorides were used to perform the reaction in the distilled water using NaOH to reach a pH of 10. The X-ray diffraction, Field Emission Scanning Electron Microscopy, Electron Dispersive X-ray and Vibrating Sample Magnetometry analyses were conducted for all samples. All samples had the patterns of the spinel structure coincide to a high degree with the Co ferrite pattern. There was a general increase in the lattice constant with the increase in the Cs content, while the crystallite size decreased from about 18 to 12.2 nm as the molar ratio increased from 0 to 0.25. The Electron Microscopy investigation showed that all samples owing spherical nanoparticles with no other shapes. The average particle sizes were between 40 to 60 nm, which increased Cs1+ content. The magnetic parameters mainly showed a relatively high coercivity (wide loops) and a decrease in magnetization saturation (down to 50.43 emu/g), crystalline anisotropic constant, and the squareness ratio.
Keywords: Cesium Cobalt Ferrite; Structural properties; Hysteresis loop; Nanoparticles; Magnetization